Evaluating Caregiver Sensitivity to Infants: Measures Matter. (27th June 2018) - Bohr, Yvonne; Putnick, Diane L.; Lee, Yookyung; Bornstein, Marc H.
Abstract : The significance of caregiver sensitivity for child development has been debated among scholars, not least due to sensitivity's inconsistent predictive value over time and across contexts. A lack of uniformity in the definition of sensitivity contributes to this debate, but shortfalls of intertool concordance and construct validity in the instruments used to assess sensitivity may also be at issue. This study examines correspondences among four established standardized measures of caregiver sensitivity in independent classifications of the same sample of mothers of infants. Fifty European American mother–infant dyads of diverse SES were independently assessed with three observational caregiver sensitivity measures: the Emotional Availability Scales (EAS; Biringen, 2008, Emotional availability ( EA ) scales manual ( 4th ed .) : Part 1. Infancy/early childhood version ( child aged 0–5 years ). Colorado State University. Unpublished manuscript), the Parent Child Interaction—Nursing Child Assessment Satellite Training Feeding Scale (PCI‐NCAFS; Oxford & Findlay, NCAST caregiver/parent‐child interaction feeding manual, Seattle, WA: NCAST Programs, University of Washington, School of Nursing, 2015), and the Maternal Behavior Q‐Sort (MBQS; Moran, Pederson, & Bento, 2009, Maternal Behavior Q‐Sort ( MBQS ) –Overview, available materials and support . University of Western Ontario. Unpublished). Ratings were juxtaposed with classifications of the same sample based on the original Ainsworth Maternal Sensitivity Scales (AMSS; Ainsworth, 1969, Power, 6, 1379). The EAS, NCAFS, and MBQS are related to the AMSS, but large proportions of variance were unshared. Researchers and clinicians should be cautious when assuming that popular observational assessment instruments, commonly believed to measure a generic construct of caregiver sensitivity, are interchangeable, as these measures may evaluate different features of sensitivity to infants.